PEMAHAMAN DAN KOMUNIKASI MATEMATIS DALAM PEMBELAJARAN MATEMATIKA REALISTIK - Siregar, Nur Fauziah (IAIN PADANGSIDIMPUAN, 2016)
Mathematics understanding and communication are two essensial competencies that should be mastered by the learners. Mathematics understanding connects pattern and its relationship, that is to connect mathematics’ concept with the laerners’ bachground knowledge. Then, mathematics communication has an important role in conveying mathematics. This is a major challenge in learning mathematics that assume to emphasize in transferring knowledge, where teachers are more dominant than learners in finding, using and elaborating knowledge. Nowdays, there are some strategies that can be used as an alternative learning to be more fun and can injluence mathematics understanding and communication of learners, such realistic mathematics education. Realistics mathematics education is a learning that shows not only the connection with the real world but also the situation that could be imagined by the learners.